Psychological Well-Being of Parents Who Have Special Needs Children and Attend Special Schools: A Qualitative Study : Kesejahteraan Psikologis Orangtua yang Memiliki Anak Berkebutuhan Khusus dan Bersekolah di Sekolah Luar Biasa : Sebuah Studi Kualitatif - Laili, Nurfi; Fahmawati , Zaki Nur; Paryontri , Ramon Ananda (Procedia of Social Sciences and Humanities, 2022)
Students with special needs are one of the conditions of a child who has different needs from other normal children. This condition of special needs, of course, makes the child also requires special handling and care processes from parents and teachers in educational institutions. On the other hand, parents as the center of parenting process are required to have a good capacity for psychological well-being, so that they can provide the right parenting process and develop the best potential of these special children. The purpose of this study was to identify the characteristics of the psychological well-being of parents who have children with special needs. Identification was carried out through in-depth interviews with several parents of children with special needs who attend SLB 'Aisyiyah Tulangan. The results of the interview show that parents have shown several characteristics of psychological well-being, namely in the aspects of self-acceptance, autonomy, environmental mastery and positive relationships with others.